Isolation, Identification, and Pathogenicity of Potential Probiotics Isolated from Intestinal Coconut Crab (Birgus latro Linnaeus, 1767) - Aris, Muhammad; Tamrin, Tamrin; Munaeni, Waode; Malan, Sudirto; Juharni, Juharni; Labenua, Rusmawati (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract The supply of coconut crabs (Birgus latro Linnaeus, 1767) has been sourced from capture in the wild. Development efforts in aquaculture have succeeded in producing eggs. However, further development with larval maintenance failed because it was constrained by a low survival rate. This study aimed to identify the potential probiotic bacteria in coconut crabs. Coconut crab samples were collected from Moor Island, South Patani District, Central Halmahera Regency, North Maluku Province, Indonesia. The intestines of coconut crabs were taken as much as 1 g, then ground on a porcelain dish and added to Tri-Salt. The scouring liquid was taken in 0.1 ml and spread on a petri dish containing Nutrient Agar. The isolated used were marked with BL1, BL2, BL3, BL4, and BL5. Molecular identification was performed with sequencing and then analyzed using the Basic Local Alignment Search Tool (BLAST). The selection of isolates from the gastrointestinal tract of coconut crabs showed that the bacteria obtained were Enterobacter tabaci (BL1), Enterobacter hormaechei (BL2), Bacillus horneckiae (BL3), Pseudomonas stutzeri (BL4), and Acinetobacter variabilis (BL5). Further testing revealed that the bacteria A. variabilis (BL5) is a probiotic isolate in coconut crabs. Highlight Research The intestinal bacteria from coconut crabs identified were E. tabaci, E. hormaechei, B. horneckiae, P. stutzeri, and A. variabilis. The E. tabaci strain BL1, E. hormaechei strain BL2, B. Horneckiae strain BL3, and P. stutzeri strain BL4 are pathogenic bacteria. The A. variabilis strain BL5 is potential probiotics bacteria. The A. variabilis strain BL5 showed a better survival rate than other isolates.